Electrically-Evoked Frequency-Following Response (EFFR) in the Auditory Brainstem of Guinea Pigs - He, Wenxin (Public Library of Science, 2014)
It is still a difficult clinical issue to decide whether a patient is a suitable candidate for a cochlear implant and to plan postoperative rehabilitation, especially for some special cases, such as auditory neuropathy. A partial solution to these problems is to preoperatively evaluate the functional integrity of the auditory neural pathways. For evaluating the strength of phase-locking of auditory neurons, which was not reflected in previous methods using electrically evoked auditory brainstem response (EABR), a new method for recording phase-locking related auditory responses to electrical stimulation, called the electrically evoked frequency-following response (EFFR), was developed and evaluated using guinea pigs. The main objective was to assess feasibility of the method by testing whether the recorded signals reflected auditory neural responses or artifacts. The results showed the following: 1) the recorded signals were evoked by neuron responses rather than by artifact; 2) responses evoked by periodic signals were significantly higher than those evoked by the white noise; 3) the latency of the responses fell in the expected range; 4) the responses decreased significantly after death of the guinea pigs; and 5) the responses decreased significantly when the animal was replaced by an electrical resistance. All of these results suggest the method was valid. Recording obtained using complex tones with a missing fundamental component and using pure tones with various frequencies were consistent with those obtained using acoustic stimulation in previous studies.